Perceptions of Professionals Working with Students with Disabilities towards the Use of E-Portfolios: Opportunities and Challenges - Alsalem, Gheed M.; Ali, Emad M.; Al-Bustanji, Murad A.; Kamal, Sana M. (Dirasat: Educational Sciences, 2021)
To keep pace with the requirements of this technological era, this study aims to propose the idea of using e-portfolios to save and present information about students with disabilities in Jordanian special education institutions. The sample consisted of 102 professionals (90 females and 12males) working with these students at six of these institutions to identify applicability and challenges associated with the creation of e-portfolios from their point of view. An example e-portfolio and a questionnaire were developed for the study. The Statistical Package for the Social Sciences (SPSS-16.0) was used to provide basic descriptive statistics for the data. In addition, an independent samples t-test was run to indicate any statistically significant differences between the means of current job variable levels. Results reflected positive perspectives toward e-portfolios. Overall feedback from the participants of the study reflected positive perspectives towards e-portfolios in the dimensions related to their effectiveness to provide quality information to serve different objectives, their uses and advantages, technical and organizational matters associated with presenting the content, and benefits that the child gains when participating in the preparation process of them. However, concerns and challenges about specific issues related development process of e-portfolios were reported. In order to take advantages of available technology, this study presents the idea of creating e-portfolios for students with disabilities at Jordanian special education institutions. The overall feedback reflects positive perspectives towards e-portfolios, the participants concern about specific issues that may arise when developing them.